Research Roadmap Development in the Field of Social Science: Exploratory Study of Social Entrepreneurship / Anang Kistyanto, Susi Handayani, Susanti, Moch. Khoirul Anwar, Ahmad Ajib Ridlwan - Kistyanto, Anang; Handayani, Susi; Khoirul Anwar, Moch.; Ridlwan, Ahmad Ajib (2021)
The industrial revolution 4.0 has implications on shifting skills and types of work. Many new skills and jobs have emerged, including social entrepreneurship skills. On the other hand, entrepreneurial social research is still limited and continues to develop. However, there is no complete social entrepreneur research model. Thus, this study aims to design a road map for social research that leads to the development of social entrepreneurship incubation. This type of research is qualitative-explorative. The data in this study are the results of analysis of documentation studies on research topics and types of social research of the relevant lecturers at the Faculty of Economics and the Faculty of Social Sciences and Law, Universitas Negeri Surabaya. The research data were analyzed through the stages of data reduction, data presentation, and conclusion. In reduction, the data is organized so that it is ready to be processed. We developed 15 main instruments in the process of forming a social entrepreneurship spirit based on systematic typology that categorizes social entrepreneurs based on their life and career experiences as well as the scope of their social engagement. Validation was carried out using the justment expert method, namely using social entrepreneurship experts from external Universitas Negeri Surabaya. The result of this research is a road map for social research, namely a social entrepreneurship development model. In addition, this research also produces academic papers related to social research topics that will produce prototypes and incubations of social entrepreneurship.